The Great Plains Interactive Distance Education Alliance - Moxley, Virginia M.; Maes, Sue C. (My University, 2009)
The landscape for higher education delivery has evolved from the traditional classroom-based, instructor-led format toward one that is internet-based and learner-led. To manage a change of this magnitude in an era of fragile public funding, universities—and higher education oversight boards and state legislatures—have discovered the potential of inter-institutional collaboration to deploy rapidly new undergraduate and postbaccalaureate programs to meet emerging needs of the professions and to target professionals seeking education for career advancement and career change. Institutions are banding together in innovative ways to capitalize on their collective and interconnected technological and human capacity, and many states have formed statewide alliances for the purpose of delivering educational courses and programs to students at a distance. The Great Plains Interactive Distance Education Alliance for the Human Sciences (Great Plains IDEA) that is described in this paper is a consortium of ten human sciences colleges located in ten states that capitalizes on the talents of inter-institutional faculty teams to offer distance education master’s degrees and postbaccalaureate certificates.
Keywords: Great Plains IDEA; Institute for Academic Alliances; Alliance Development; Higher Education; Educaional Consortia; Consortia Foundations